Validation of the Malay Version of the Sources of Social Support Scale among Malaysian Cancer Patients - Abdullah, Mohammad Farris Iman Leong; Hami, Rohayu; Azman, Nizuwan; Mohd Shariff, Noorsuzana; Appalanaido, Gokula Kumar; Md Sharif, Siti Shahanis (ASEAN Federation of Psychiatry and Mental Health (AFPMH), 2017)
Objective: It is important to investigate the association between spousal support and psychology of cancer patients, thus a validated instrument to measure the degree of perceived spousal support is required. We translated and evaluated the psychometric properties of the Sources of Social Support Scale-Malay version (SSSS-Malay) among Malaysian cancer patients. Methods: In this study, the SSSS-Malay and Hope Scale-Malay [used to compare with the SSSS-Malay to assess discriminant validity] were administered to 195 Malaysian cancer patients during baseline assessment. The SSSS-Malay was re-administered 2 months after the baseline assessment during follow-up. Results: The SSSS-Malay total score (Cronbach’s α = 0.70, intraclass correlation coefficient (ICC) = 0.72) and its domains (Cronbach’s α ranging from 0.70 to 0.83, intraclass correlation coefficient ranging from 0.6 to 0.76) exhibited good internal consistencies and good test-retest reliability. The SSSS-Malay also demonstrated good convergent and discriminant validities. However, confirmatory factor analysis of the SSSSMalay showed that it was best fit into a 3-factor model instead of the 4-factor model of the original English version. Conclusion: The SSSS-Malay demonstrated good psychometric properties for use in Malaysian cancer patients.